Horizontal industry relationships and return predictability - Christian Schlag; Kailin Zeng (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
It has been documented that vertical customer-supplier links between industries are the basis for strong cross-sectional stock return predictability (Menzly and Ozbas (2010)).We show that robust predictability also arises from horizontal links between industries, i.e., from the fact that industries are competitors or offer products, which are substitutes for each other. These horizontally linked industries exhibit positively correlated fundamentals. The signal derived from this type of connectedness is the basis for significant alpha in sorted portfolio strategies, and informed investors take the related information into account when they form their portfolios. We thus provide evidence of return predictability based on a new type of economic links between industries not captured in previous studies.
urn:nbn:de:hebis:30:3-507368
Keywords: G12; E44; D81; 330; connected industries; information flow; return predictability